He-man and the masters of the universe Season Three - Lowenthal, Yuri; Rio, Antony Del; Diskin, Ben; Mill Creek Entertainment (United States Mill Creek Entertainment, 2023)
Season three. Episodes include: The Haunting Of Castle Grayskull; Frozen Solid; The Wrath Of Mer-Man; The Tomb Of Grayskull; A Leap Of Faith; In-Can't-Ation; The Beginning Of The End, Part 1; The Beginning Of The End, Part 2.
The haunting of Castle Grayskull -- Frozen solid -- The wrath of Mer-Man -- The tomb of Grayskull -- A leap of faith -- In-can't-ation -- The beginning of the end, part 1 -- The beginning of the end, part 2.
Title from container.
Wide screen (1.85:1)
Originally broadcast as single episodes of a television program in 2022.
Yuri Lowenthal, Antony Del Rio, Ben Diskin, Grey Griffin, Kimberly Brooks, David Kaye, Tom Kenny.
Rating: TVY7.
DVD, region 1, NTSC; wide screen (1.85:1); 2.0 Dolby Digital.
Keywords: He-Man -- (Fictitious character) -- Juvenile films; She-Ra -- (Fictitious character) -- Juvenile films; Princes -- Juvenile films; Heroes -- Juvenile films; Good and evil -- Juvenile films; Imaginary places -- Juvenile films; Imaginary wars and battles -- Juvenile films; Animated television programs; Children's films; Children's television programs; Fiction television programs; Juvenile works; Television programs; Video recordings for the hearing impaired